An Appraisal of Arsenic and Pesticide Toxicity for Economically Terminal People: a Snap Shot of North-Western Part of Bangladesh (Journal of Scientific Research, 2015)
The aims of this study were to detect the levels of arsenic (As) and selected organophosphorus pesticides (OPPs) in the drinking water and the water from surface sources, respectively for a small section of poor people of the country Bangladesh, and to relate the levels of these offensive chemicals with their acute physical ailments. Mean levels of As in drinking water from tube wells are found 0.1 ± 0.01 mg L-1, which are nearly ten times higher than the maximum tolerable limits for humans. Correlation studies suggest that higher level of As is significantly correlated with total dissolved solids (TDS) and with few more water quality parameters investigated here. Similar to that, residues of selected OPPs in surface water of the area are also found several fold higher (0.24 - 0.48 µg L-1) than the expected levels, and if the suspended solids of that water are considered then the residue levels would have been further higher. This study has a merit for its findings regarding As toxicity as well as possible OPPs contamination in the investigated area, and suffering of the people from both exposures in relation with their poor economical power is addressed.